Cigarette Excise: Between State Revenue And Global Demands - Carl Augustinus Hothinca Soutihon Tampub; Detania Sukarja; T. Keizerina Devi Azwar (JURNAL HUKUM SEHASEN, 2024)
One of the state revenues comes from excise tax, especially tobacco products, namely cigarettes. However, a breakthrough or certain steps are needed so that state revenue can be obtained optimally. Globalization has responded to the existence of excise, especially from cigarette products as a country's income. In addition, the law is also required to play a role in providing certainty, expediency and justice in terms of responding to the existence of excise tapes as a sign of payment of excise. Therefore, through this research, it will be described how the role of excise as state revenue and the development of cigarette excise in the global environment. Then, as a tool to test this scientific paper, it uses a type of juridical-normative research with a statutory approach. In addition, to enrich this research, primary data will be used from books, journals and so on and secondary data will be added as a complement to this research. The results of this study, the hope is based on the mechanisms owned by several countries, so that Indonesia can follow the pattern as a tangible form to increase more state revenue.